1994
DOI: 10.1159/000119074
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Alpha<sub>2</sub>-Adrenergic Receptor Binding and the Effects of <i>d</i>-Amphetamine in Boys with Attention Deficit Hyperactivity Disorder

Abstract: Presynaptic inhibitory alpha-adrenergic receptors are involved in regulating the release of norepinephrine (NE) through a negative feedback mechanism mediated by NE. Increased alpha2-adrenergic receptor activity suggests decrease NE release and activity, while decreased alpha2-adrenergic activity suggests increase NE release and activity. A large body of evidence suggests the involvement of a disturbance in NE activity in the pathophysiology of attention deficit hyperactivity disorder (AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…In fact, clonidine, which decreases NE activity, has been reported to be of benefit in ADHD and is now in a Phase III clinical trial for treatment of ADHD (http://clinicaltrials.gov/show/NCT00031395). Our evidence suggests that a decrease in α2-adrenergic autoreceptor control of NE activity underlies noradrenergic hyperfunction in our rat model of prenatal cocaine, so it is interesting that a similar deficit appears to occur in the spontaneously hypertensive rat model of ADHD (Russell, 2002) and that a decreased density and decreased affinity of binding to α2-adrenergic sites have been reported in ADHD (Shekim et al, 1994;Deupree et al, 2006). Moreover, there is evidence supporting association and linkage of α2A-adrenergic receptor gene polymorphisms with ADHD (Park et al, 2005).…”
Section: Discussionsupporting
confidence: 60%
“…In fact, clonidine, which decreases NE activity, has been reported to be of benefit in ADHD and is now in a Phase III clinical trial for treatment of ADHD (http://clinicaltrials.gov/show/NCT00031395). Our evidence suggests that a decrease in α2-adrenergic autoreceptor control of NE activity underlies noradrenergic hyperfunction in our rat model of prenatal cocaine, so it is interesting that a similar deficit appears to occur in the spontaneously hypertensive rat model of ADHD (Russell, 2002) and that a decreased density and decreased affinity of binding to α2-adrenergic sites have been reported in ADHD (Shekim et al, 1994;Deupree et al, 2006). Moreover, there is evidence supporting association and linkage of α2A-adrenergic receptor gene polymorphisms with ADHD (Park et al, 2005).…”
Section: Discussionsupporting
confidence: 60%
“…However, the significant correlation with severity among affected boys was negative. One earlier study has shown that ADHD boys tended to have a lower alpha-2 adrenergic receptor density [Shekim et al, 1994]. Nevertheless these results indicate the possibility of a polymorphism in the regulatory regions of the alpha-2 adrenergic receptor gene associated with ADHD.…”
Section: Discussionmentioning
confidence: 65%
“…Further studies which include gene function phenotypes as well as more complete behavioral assessments may help define the phenotypes that are most affected by a given candidate gene. Radioligand binding assays of the alpha-2A adrenergic receptor on human platelets are commonly used to study the involvement of the noradrenergic system in various psychiatric disorders including depression, schizophrenia, and ADHD [Katona et al, 1989;Karege et al, 1992;Piletz et al, 1993;Shekim et al, 1994;Maes et al, 1999;Gurguis et al, 1999a;Odagaki and Koyama, 2002]. Previous studies have noted the problems associated with the day-to-day variability of this assay as well the variability of the binding parameters among subjects [Reimann et al, 1987].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amphetamine is known to not alter the binding of yohimbine to peripheral α 2 R on platelets, as reported for humans. 17 Therefore, we performed plasma ultrafiltration to test the hypothesis that amphetamine does not affect plasma protein binding as reflected in measures of the plasma-free fraction, in support of the assumption underlying the Inhibition plot that the values of V ND are unchanged.…”
Section: Methodsmentioning
confidence: 94%